Testimonios on participatory action research as a critical race approach to studying Southeast Asian american Refugee subjects - Nguyen, Angela‐MinhTu D.; Huynh, Que‐Lam; Chang, Richard; Lieng, Nathan (Journal of social issues, 2024)
Instead of being agents of inquiry and change, Southeast Asian American (SEAA; Viet, Hmong, Lao, Cambodian) refugee subjects are often objectified and essentialized by researchers in the social sciences. In this article, we document our collaborative journeys to unlearn colonial and racist ways of thinking about and conducting research on marginalized communities, including our own SEAA communities. Specifically, we present participatory action research (PAR) and testimonios—two examples of counter‐storytelling—as promising critical race methodologies. Using PAR, our team of academic researchers and participant‐researchers collaborated on research to create change in our communities. To assess our experiences with PAR, we used testimonios to share our self‐reflections and stories on the research process and the training relationship. We end by offering suggestions for using PAR and testimonios to engage in anti‐colonial and anti‐racist research.